Head and Neck Manifestations of Necrotizing Fasciitis: A Case Series and Meta-Analysis. Issue 2 (June 2023) - Yan, Derek; Holan, Cole; Padilla, Pablo L.; Ramtin, Sina; Shah, Darsh; Hancock, Ellen; Thyagarajan, Rama; Combs, Patrick; Harshbarger, Raymond
Introduction: Plastic surgeons frequently take facial trauma calls, and their responsibilities may include infection care. The head and neck is a site of presentation for necrotizing fasciitis which requires a high level of suspicion and prompt acti2on for diagnosis and treatment. We performed a meta-analysis of the literature on necrotizing fasciitis of the head and neck (HNnf) to summarize clinical factors, causative organisms, and treatment, and included 2 cases presenting to our institution. Methods: A meta-analysis of the literature from 1990 to 2021 was completed on HNnf. After institutional review board approval, medical records of 2 patients presenting with a diagnosis of HNnf to an academic plastic surgery center between July and September 2021 were retrospectively reviewed. Systematic reviews and articles without comprehensive individualized patient data were excluded. Results: A systematic review was performed including 2 cases presenting to our institution. A total of 149 individual cases of HNnf spanning a 30-year period were included. The most common associated comorbidity was diabetes mellitus. The most frequent source of infection was odontogenic. Most patients required serial debridements in addition to IV antibiotics. Streptococcus pyogenes was the most frequent pathogen; however, most infections were polymicrobial. Infections in the periorbital region were significantly monomicrobial ( P = .011). Acute reconstructive surgery requirements: 27 patients had skin grafting, 9 had flap reconstruction. Mortality rate was 12.3%. Increasing age was a significant predictor of mortality ( P = .01). Patients with diabetes were significantly more likely to die from HNnf (52.6%, P = .039) and require multiple debridements ( P = .001) for HNnf as compared to patients without diabetes. Infections initially arising from the submandibular region were found to be an independent negative predictor of mortality ( P = .029). Conclusion: Our experience with HNnf along with meta-analysis of the literature revealed trends in demographics, presentation, organisms, and outcomes, increasing the collective knowledge of this rare entity.